Communication and education in health consultations to children with acute respiratory infections - Carvalho, Ana Paula Alves de; Veríssimo, Maria De La Ó Ramallo (Revista da Escola de Enfermagem da USP, 2011)
The objective of this study was to identify the recommendations for the care of children with acute respiratory infections (ARI) and to describe the process of communication between professionals and mothers during the consultation. Data collection was performed in Primary Care Units, through interviews and observation of physicians' and nurses' consultations to children with ARI. The recommendations ranging between professionals and were incomplete and focusing on the disease, mainly on the treatment; communication is focused on the professional, which does not promote an emancipatory education process. The results confirmed the need to include such issues in the initial and ongoing training of professionals.